The Question Concerning Comics as Technology: Gestell and Grid. Issue 1 (24th September 2018) - Priego, Ernesto; Wilkins, Peter
In this article we argue that the comics grid, the array of panels, can be understood as a specific technology of 'revealing' through 'enframing' and as such is the key element in comics technology. We propose Martin Heidegger's conceptual framework ( Gestell : literally, 'the framework'), primarily discussed in his 1954 essay 'The Question Concerning Technology' (1982 ) as a strategy that can be used to engage critically with panel layout in graphic narratives, concluding that the role of the grid in comics and the way that new technologies put that grid to work both in the production and consumption of comics means that comics embody the relationship between technology, storytelling and materiality. In an age in which most of the screens that dominate our information-filled lives are rectangular, we argue that the purpose of the grid is to manage a potentially overwhelming sublime space.